O socialismo do século XXI e a integração sul-americana: caminhos possíveis - Araujo, Rafael Pinheiro de (2010)
South America witnessed the emergence of political projects to build a new socialism, called Socialism of the XXI century. This presents new socialism, as the main constituent elements, popular mobilization, economic nationalism and the construction of new projects of regional integration. In this sense, indigenous and Bolivarian link to an integration of "people of the south", but with paths, and even ends, distinct. Seek the indigenous pre-Columbian past the driving force of integration prospects. Already the Bolivarian develops an integration project based on speech and image of one of the heroes of the independence of South American nations against Spain, Simon Bolivar. In this perspective, to compare the integration projects of indigenous and Bolivarian, and seeks a definition of the new socialism.